# Find dy/dx by implicit differentiation. 7x2 + 5xy − y2 = 8?

### 9 Answers

- PinkgreenLv 74 weeks agoFavourite answer
7x^2+5xy-y^2=8

=>

14x+5y+5xy'-2yy'=0

=>

(5x-2y)y'=-(14x+5y)

=>

y'=-(14x+5y)/(5x-2y)

- Log in to reply to the answers

- ComoLv 74 weeks ago
7x² + (5x) y - y² = 8

14x + 5y + dy/dx (5x) - 2y dy/dx = 0

( 5x - 2y ) dy/dx = - (5y + 14x)

dy/dx = - (5y + 14x) / (5x - 2y)

- Log in to reply to the answers

- PhilipLv 64 weeks ago
7x^2 +5xy -y^2 = 8. Implicit differentiation gives 14x +5(xy'+y) = 2yy', ie., 14x+5y =

(2y-5x)y'. Then y' = (14x+5y)/(2y-5x) = -(14x+5y)/(5x-2y).

- Log in to reply to the answers

- King LeoLv 74 weeks ago
7x² + 5xy - y² = 8

14x + 5xy’ + 5y - 2yy’ = 0

( 2y - 5x )y' = ( 5y + 14x )

y' = ( 5y + 14x )/( 2y - 5x )

dy/dx = ( 5y + 14x )/( 2y - 5x )

—————————————

- Log in to reply to the answers

- What do you think of the answers? You can sign in to give your opinion on the answer.
- lenpol7Lv 74 weeks ago
14x + 5y + 5xdy/dx - 2ydy/dx = 0

14x + 5y + dy/dx (5x - 2y) = 0

dy/dx((5x - 2y) = -14x - 5y

dy/dx = (-14x - 5y) / ((5x - 2y)

- Log in to reply to the answers

- Φ² = Φ+1Lv 74 weeks ago
d(7x²)/dx = 14x

d(5xy)/dx = 5y + 5x(dy/dx)

d(y²)/dx = 2y(dy/dx)

d(8)/dx = 0

7x² + 5xy - y²= 8, so

14x + 5y + 5x(dy/dx) - 2y(dy/dx) = 0

(5x - 2y)(dy/dx) = -14x - 5y

dy/dx = (-14x - 5y)/(5x - 2y)

- Log in to reply to the answers

- Engr. RonaldLv 74 weeks ago
7x^2 + 5xy − y^2 = 8

14x + 5(y * 1 + xdy/dx) - 2ydy/dx = 0

14x + 5y + 5xdy/dx - 2ydy/dx = 0

5xdy/dx - 2ydy/dx = - 14x - 5y

dy/dx(5x - 2y) = - 14x - 5y

............... - 14x - 5y...............14x + 5y

dy/dx = ------------------- or - ---------------- answer//

................... 5x - 2y.................5x - 2y

- Log in to reply to the answers

- BryceLv 71 month ago
7x² + 5xy - y²= 8

14x + 5x*dy/dx + 5y - 2y*dy/dx= 0

dy/dx(5x - 2y)= -(14x + 5y)

dy/dx= -(14x + 5y)/(5x - 2y)

- Log in to reply to the answers

- la consoleLv 71 month ago
7x² + 5xy - y² = 8

7x² + 5xy - y² - 8 = 0

7x² + 5xy - y² - 8 = 0 → when x is constant: → (5x - 2y).dy = 0

7x² + 5xy - y² - 8 = 0 → when y is constant: → (14x + 5y).dx = 0

(5x - 2y).dy + (14x + 5y).dx = 0

(5x - 2y).dy = - (14x + 5y).dx

dy/dx = - (14x + 5y)/(5x - 2y)

- VamanLv 74 weeks agoReport
Good answer.

- Log in to reply to the answers